FOXE3 mutations: genotype‐phenotype correlations. Issue 4 (14th March 2018) - Plaisancié, J.; Ragge, N.K.; Dollfus, H.; Kaplan, J.; Lehalle, D.; Francannet, C.; Morin, G.; Colineaux, H.; Calvas, P.; Chassaing, N.
Abstract : Microphthalmia and anophthalmia (MA) are severe developmental eye anomalies, many of which are likely to have an underlying genetic cause. More than 30 genes have been described, each of which is responsible for a small percentage of these anomalies. Among these, is the FOXE3 gene, which was initially described in individuals with dominantly inherited anterior segment dysgenesis and, subsequently, associated with recessively inherited primary aphakia, sclerocornea and microphthalmia. In this work, we describe 8 individuals presenting with an MA phenotype. Among them, 7 are carrying biallelic recessive FOXE3 mutations and 2 of these have novel mutations: p.(Ala78Thr) and p.(Arg104Cys). The last of our patients is carrying in the heterozygous state the recessive p.(Arg90Leu) mutation in the FOXE3 gene. To further understand FOXE3 involvement in this wide spectrum of ocular anomalies with 2 different patterns of inheritance, we reviewed all individuals with ocular abnormalities described in the literature for which a FOXE3 mutation was identified. This review demonstrates that correlations exist between the mutation type, mode of inheritance and the phenotype severity. Furthermore, understanding the genetic basis of these conditions will contribute to overall understanding of eye development, improve the quality of care, genetic counseling and, in future, gene‐based therapies. Abstract : Phenotype and genotype of 123 patients (38 index cases and 85 family members) with a total of 20 different FOXE3 mutations